The Effectiveness Of The State Asset Management And Accounting Information System (Simak-Bmn) Implementation At The Tigaraksa Religious Court - Siti Ratna Sari Dewi; Desi Pratiwi (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to evaluate the effectiveness of the State Asset Management and Accounting Information System (SIMAK-BMN) at the Tigaraksa Religious Court. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The focus of the study includes user satisfaction, system quality, information quality, internal control, and auditor opinion. Findings reveal that SIMAK-BMN is effective in supporting asset management processes and generating reliable financial information. Users reported satisfaction in terms of system usability and functionality, although they highlighted a lack of formal training. The system ensures information security and has contributed to the institution’s ability to obtain unqualified audit opinions. However, technical issues during system updates were identified as a concern that may affect reporting timeliness and administrative order. The study recommends periodic evaluations and improved system readiness during updates to enhance operational efficiency. These findings offer insights for public institutions in managing state assets through digital systems.